Immunohistochemical Expression of Platelet-Derived Growth Factor Receptors in Ovarian Cancer Patients with Long-Term Follow-Up - Madsen, Christine Vestergaard (Hindawi Publishing Corporation, 2012)
Introduction. The well-documented role of the PDGF system in tumor growth and angiogenesis has prompted the development of new biological agents targeting the PDGF system. The aim of the present study was to analyze the expression of the PDGF-receptors in ovarian cancer and to investigate its relation to histopathological parameters and long-term overall survival. Methods. The immunohistochemical expression of PDGFR-α and PDGFR-β was investigated in tumor and stromal cells in 170 patients with histologically verified epithelial ovarian cancer. Results. Almost half of the tumor specimens showed high expression of PDGFR-α and PDGFR-β in tumor cells (43% and 41%) and in stromal compartments (32% and 44%). There was a significant association between high expression of PDGFR-α and high expression of PDGFR-β in both tumor and stromal cells. Coexpression of PDGFR-α and PDGFR-β in stromal cells was seen more often in serous adenocarcinomas than in nonserous adenocarcinomas. No clear correlation between PDGFR expression and longterm overall survival or clinical parameters was found. Conclusions. PDGFR-α and PDGFR-β were expressed in a subset of ovarian carcinomas but did not show significant prognostic importance in this material.